The Artistic Conversation: An ABR Multimodal Qualitative Innovation - Dina Fried (International Journal of Qualitative Methods)
This paper introduces “artistic conversation,” a novel qualitative arts-based research (ABR) methodology integrating creative writing, visual art, and video documentation to explore lived experiences of adults with ADHD. Conducted over five iterative sessions with four participants, this pilot study advances qualitative inquiry by demonstrating how multimodal dialogue—where researchers co-create art with participants—elicits sensory-rich insights beyond traditional methods. Effectiveness was evaluated through participant reflections, artistic evolution across sessions, and comparisons with verbal methods, revealing deeper sensory and relational understanding. Key innovations include GoPro documentation capturing creators’ perspectives and blended modalities for embodied insights. Participants, positioned as co-researchers, shaped outcomes, fostering inclusivity through collaborative agency, assessed via feedback on trust and reciprocity. Ethical approval ensured consent, protecting neurodiverse voices. The transparent, reproducible process—spanning recruitment, data collection, and integrative analysis—offers a rigorous model for qualitative research, with GoPro reducing extraneous data. Despite a small sample, its adaptability suggests potential for neurodiversity scholarship, warranting further exploration in larger studies.